SÍNTESE E CARACTERIZAÇÃO DA MESO-TETRAKIS(4-METÓXIFENIL)PORFIRINA E DERIVADOS - Scheid, Silvia (2009)
The development of methods for the synthesis of porphyrins has been studied since 1929. Since then, several studies were carried out in order to increase yield and lower the production costs. This work describes a process, based on Adler-Longo method, in which propionic acid was replaced by a mixture of by acetic acid and acetic anhydride on the synthesis of meso-tetrakis(4-methoxyphenyl)porphyrin 16. The process is attractive because the yield was improved, the cost lowered and removal of the solvent was easier because of the low boiling point. The formation of porphyrins complexed with metals, such as, iron 17, manganese 18, copper 19 and zinc 20, was also studied with success. The methods found in the literature were modified to facilitate the process of reaction and purification. The synthesis of metalloporphyrins was performed without the use of inert atmosphere, and the performance found was consistent with those described in literature for the iron and copper metalloporphyrins, but the purification process was facilitated. Copper metalloporphyrin 19, precipitates in N,N-dimethylformamide (DMF), and therefore, filtration was a simple and effective method of purification. The porphyrin and metalloporphyrins were fully characterized by infrared, UV-Vis and electron paramagnetic resonance (EPR) and nuclear magnetic resonance (RMN) spectroscopy. All the spectral data were completely consistent with those reported in the literature. Synthesized compounds.